2023
DOI: 10.1111/bjh.18842
|View full text |Cite
|
Sign up to set email alerts
|

Sustained response off treatment in eltrombopag for children with persistent/chronic primary immune thrombocytopenia: A multicentre observational retrospective study in China

Abstract: Immune thrombocytopenia (ITP) is an acquired immune disorder characterized by reduced platelet (Plt) production and increased platelet destruction, which increases bleeding risk, with a prevalence of 5 in 100 000 children. 1,2 Although it does have a high rate of spontaneous remission, 30%-40% of cases of persistent or chronic immune thrombocytopenia (p/cITP) lead to heavy bleeding. 3,4 Thrombopoietin receptor agonists (TRAs) have emerged as the best treatment to elevate and maintain the Plt count for children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Eltrombopag stimulates thrombopoiesis and is considered suitable for use in in pediatric patients [21] . In our study, 67.0% of patients achieved OR, 55.3% of patients achieved CR, 11.7% of patients achieved R, which is consistent with previously reported for children with ITP [22] .Although, our OR rate is lower than what has been reported in the children with chronic ITP [18] .During the follow-up period, we observed a considerable number of parents had high expectations for the platelet count, leading to the poor compliance. Three children discontinued the treatment at 1 week and four children at 2 weeks.…”
Section: E Cacy Of Eltrombopag Under Six Months Patientssupporting
confidence: 92%
“…Eltrombopag stimulates thrombopoiesis and is considered suitable for use in in pediatric patients [21] . In our study, 67.0% of patients achieved OR, 55.3% of patients achieved CR, 11.7% of patients achieved R, which is consistent with previously reported for children with ITP [22] .Although, our OR rate is lower than what has been reported in the children with chronic ITP [18] .During the follow-up period, we observed a considerable number of parents had high expectations for the platelet count, leading to the poor compliance. Three children discontinued the treatment at 1 week and four children at 2 weeks.…”
Section: E Cacy Of Eltrombopag Under Six Months Patientssupporting
confidence: 92%
“…However, this finding may provide an idea and direction for further exploring the sensitizer of TPO-RAs, as about 37% of patients had no response or relapse after discontinuing TPO-RAs in our previous study. 13 Sun's study found that the addition of diacerein as a sensitizer to ELT has improved the initial response for ELT-inefficient or relapsed ITP patients by increased the level of TGF-β and promoted megakaryocyte PI3K phosphorylation. 14 The previous study also showed COVID-19 significant increase in the tissue biomarkers of TGF-β in the paraffin lung samples from patients who died of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…9 The median time to first response was >12 days in a children's eltrombopag study, 16 and the median time to first response was 16 days in our previous eltrombopag study. 17 In this study, the median time to first response (platelet count ≥30 × 10 9 /L with at least a twofold increase from baseline and no bleeding at 4 weeks) was 7 days. This study also showed that attaining the required platelet levels was slightly quicker than that observed in our previous AVA switch study, in which the median time to response was 21 days.…”
Section: Discussionmentioning
confidence: 55%